The Role of Naphthaleneacetic Acid and 1-Methylcyclopropene in Preventing Preharvest Berry Dropping in Vitis vinifera L. - Antonio Carlomagno; Claudio Bonghi; Giuseppe Montanaro; Alessandra Ferrandino; Angela Rasori; Vitale Nuzzo; Vittorino Novello (Plants)
Fruit dropping represents a concern in many fruit species, including Vitis vinifera L. This research investigated the role of two plant growth regulators (PGRs), naphthaleneacetic acid (NAA) and 1-methylcyclopropene (1-MCP), in mitigating preharvest berry dropping (PHBD) through affecting ethylene (ET) and auxin (AUX) metabolism and interactions, key hormones involved in abscission. The experiment was carried out on cv. Dolcetto, with PGR treatments applied at 43, 53, and 90 days after anthesis (DAA) for NAA and at 56 DAA for 1-MCP. Berry dropping incidence, yield parameters, and transcript levels of genes related to ET and AUX pathways were analyzed, including VIT_212s0059g01380, VIT_211s0016g02380, VIT_207s0005g00820, VIT_216s0013g00980, VIT_203s0091g00310, and VIT_207s0104g00800. Both NAA and 1-MCP significantly reduced PHBD, with NAA achieving a 92% reduction and 1-MCP an 82% reduction compared to control vines. Transcript analysis revealed differential gene expression patterns, indicating that NAA affects the ET biosynthesis pathway, while 1-MCP interferes with ET receptor signaling. The results suggest that both PGRs effectively reduced berry dropping, providing a basis for integrated crop management strategies to mitigate PHBD in grapevine cultivars susceptible to this physiological disorder.